Pengembangan Media Pembelajaran Berbasis Android pada Mata Kuliah Pemrograman Visual dengan Metode Addie - Juanda, Yeni Marita; Hendriyani, Yeka (Jurnal Vokasi Teknik Informatika, 2022)
Learning media is a medium used to support learning and teaching proccess. Through the use of learning media, both educators and students can be facilitated by using learning media. The development of learning media aims to improve the quality and quantity of understanding and comprehending of a teaching material for each student. The learning media in the Visual Programming course of the Informatics Engineering Education Study Program, Department of Electronics Engineering, FT UNP usually uses a jobsheet. Since the Corona Virus Disease 2019 (Covid-19) pandemic, the lecture process for these courses, both lecturers and students, has been facing several problems. One of the problems experienced is that direct interaction in the FT UNP Laboratory cannot be carried out when doing this practicum. According to the problems occured, it is required to develop a learning media. The solution given to these problems is to develop a video tutorial-based learning median. Development of video tutorial-baseds learning median aims to support the learning process in Visual Programming courses for students of the Informatics Engineering Education Study Program. The method used in the development of this learning media is ADDIE. Video tutorial-based learning media developed by utilizing Camtasia Studio 8.0 and Android Studio as the main tools. This learning media provides several main menus including RPS, materials, videos, quizzes, scores, and about. Through this learning media application, both students and lecturers will be helped in organizing teaching and learning activities both online and offline.